Steady State Learning and Nash Equilibrium - Fudenberg, Drew; Levine, David K. (Econometrica, 1993)
We study the steady states of a system in which players learn about the strategies their opponents are playing by updating their Bayesian priors in light of their observations.Players are matched at random to play a fixed extensive -form game, and each player observes the realized actions in his own matches, but not the intended off -path play of his opponents or the realized actions in other matches.If lifetimes are long and players are very patient, the steady state distribution of actions approximates those of a Nash equilibrium.